Pengembangan Lembar Kegiatan Mahasiswa Berbasis Eksperimen Pada Materi Pencemaran Lingkungan - Fitriani Fitriani (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: The characteristic of the material of environmental pollution requires the real object from surrounding as learning resources. Hence, it demands the students move in or out of the classroom activity. Therefore, it is required to develop a student’s worksheet based on experiments that are expected to explain the theory about nature that can be revealed by experimental activities, especially on the material of environmental pollution. This study was Research and Development from the thiagarajan model of 4 D (Define, Design, Development and Disseminate). However, this study was conducted until the development stage only without the disseminate stage, because this study did not use it for a large scale. The instruments used in this study were validation sheets and respondent questionnaires for student’s worksheets based on experiments. The result of this study showed that the validity percentage based on the value of three expert validators with an average of 93,52 % included the very valid category. Meanwhile, the average percentage results of the respondent questionnaire included very applicable category from the first and the second tryouts were 90,98 % and 89,16 %, respectively. In conclusion, student’s worksheet based on experiments can be stated as the teaching materials which has been validated and very applicable to be used in the learning process. Keywords: Student’s worksheet based on experiments; Environmental pollution; Development